Nineteen Bible Atlases Compared (The Biblical archaeology review, 1983)
The map illustrations with this atlas review are reproduced exactly the same size as they appear on the atlas pages. In most instances we have chosen comparable map sections so that readers may easily compare type and line quality, topographical rendering, and historical, Biblical and geographical information. The Historical Geography of the Holy Land